2023
DOI: 10.3389/fpsyg.2023.1163382
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the 10-item Connor-Davidson Resilience Scale in Chinese military personnel

Zhihao Tu,
Jingwen He,
Ziying Wang
et al.

Abstract: BackgroundThe 10-item Connor-Davidson Resilience Scale (CD-RISC-10) is a widely used assessment of resilience. However, psychometric properties of the Chinese version of CD-RISC-10 have not been well investigated in a Chinese military personnel sample.MethodsA total of 3,129 Chinese military personnel completed the CD-RISC-10, Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS). Among them, 528 recruits completed the CD-RISC-10, SAS, and SDS again after 3-month basic military training (BMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 87 publications
2
6
0
Order By: Relevance
“…The results of our CFA are consistent with the findings of other studies confirming the single-factor model of the tool. Numerous studies support our finding that the CD-RISC-10 is a unidimensional tool for measuring resilience [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Our study investigated, for the first time, the validity of the CD-RISC-10 using a sample of nurses.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The results of our CFA are consistent with the findings of other studies confirming the single-factor model of the tool. Numerous studies support our finding that the CD-RISC-10 is a unidimensional tool for measuring resilience [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Our study investigated, for the first time, the validity of the CD-RISC-10 using a sample of nurses.…”
Section: Discussionsupporting
confidence: 83%
“…Afterwards, several studies examined the psychometric properties of the CD-RISC-10 in different populations, settings, and cultures. In particular, Tu et al confirmed the single-factor model of the CD-RISC-10 in a Chinese military personnel sample [ 50 ]. Also, they found that the CD-RISC-10 had good concurrent and predictive validity using an anxiety and depression scale [ 50 ].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations